THE COLLABORATIVE GOVERNANCE APPROACH TO PREVENTING AND ADDRESSING CHILD MARRIAGE IN BONDOWOSO REGENCY - Qomariyah, Nuril; Salam, Miftahus (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
The increase of the legal marriage age to 19 triggered a surge in marriage dispensations in Bondowoso Regency (1,045 rulings in 2020). However, a significant 41.89 % decline occurred in 2023 and 2024 after the implementation of a collaborative policy that required psychological and medical assessments. The effectiveness of this reduction in dispensations demonstrates the success ofcollaborative governance, but it also highlights the need to integrate traditional religious leaders and other local actors into an inclusive collaboration model to deconstruct cultural norms and reinforce holistic prevention of child marriage. This study is crucial for examining contextual collaboration through a Collaborative Governance approach in Bondowoso Regency to curb child marriage. It explores the collaborative roles of local government, religious leaders, and community figures in preventing and addressing child marriage. Grounded in qualitative phenomenology, the research focuses on two villages each from five subdistricts of Bondowoso (Maesan, Wringin, Sumberwringin, Tapen, and Curahdami). Data were collected through initialmapping FGDs, in-depth interviews, observation, and documentation, and then analyzed using an interactive model. The study’s findings are as follows: 1) Implementation of the Marriage Dispensation Policy and Its Impact on Child Marriage Rates in Bondowoso Regency; 2) Persistence of Child Marriage Practices Following the Reduction in Dispensations in Bondowoso Regency; 3) A Collaborative Governance Model for the Prevention and Handling of Child Marriage; 4) Optimization of Best Practices in Child Marriage Prevention; and 5) Supporting Factors for the Persistence of Child Marriage in Bondowoso. Efforts to reduce child marriage in Bondowoso require the integration of formal policy, cultural approaches, and socio-economic empowerment. Inclusive multi-stakeholder collaboration is key to bridging the gap between regulation and social practice.